Experimental Investigation on the Influence of the Location of Sand Mining on the Local Scour Characteristics of Bridge Piers - WU Wei; CAI Huiyi; WANG Hao; FU Dabao; CHEN Zetong; YAO Jiateng (工程科学与技术)
ObjectiveThe existence of sandpits in the river will affect the stability of piers. There are few studies on the relationship between the two, and further research is needed. In this paper, two kinds of flow conditions, four kinds of sand pit positions and local scour tests of piers without sand pit structures were carried out, and the characteristics of scour topography and the variation of local turbulent structure of piers under different working conditions were analyzed.MethodsFirstly, the three-dimensional terrain reconstruction is carried out by using Visual SFM open source software, and the Scale Invariant Feature Transformation method is used to identify and extract the terrain feature points, and the feature points are matched. The photo group taken by the camera is sorted and the feature points are identified according to the location information of the photo, and the feature points of different photos are matched to obtain the homonymous points. Based on the matching feature points, the sparse point cloud and dense point cloud of the model are obtained in turn. The result error is ±0.1mm and the accuracy is high. Secondly, in order to obtain the flow field information near the pier, the instantaneous flow field is calculated by using the formula to obtain the time average velocity field, so as to analyze the flow characteristics around the pier. At the same time, in order to better understand the flow characteristics of the local flow field of the pier, the Snapshot POD method is used to decompose the instantaneous flow field obtained by the PIV device into the average flow field and the pulsating flow field, and the pulsating flow field is decomposed, and the first several modes with higher energy are extracted for comparison.Results and Discussions The structural characteristics of the local scour pit of the pier are quantitatively studied. Due to the clear water erosion, the flow velocity is lower than the sediment start-up velocity, and the upstream bed surface elevation of the pier is relatively flat. Due to the flow velocity is greater than the sediment start-up velocity, the bed surface sand transport causes the bed surface topography to rise and fall. The closer the upstream is to the pier column, the two-dimensional profile of the bed elevation gradually decreases until the maximum pit depth of the pier scour pit. The upstream dip angles αU1 and αU2 of the sand pit are basically the same and are basically consistent with the sediment repose angle. The scour hole is basically symmetrical along the symmetry axis plane of the pier model, that is, the angle αL=αR between the elevation profile line and the transverse Y axis. The closer the distance between the sand pit and the pier model, the greater the depth of the pier scour pit, and the depth of the riverbed under the high flow intensity is greater than that of the low flow intensity. As the distance between the sand pit and the pier model is different, the maximum pit depth of the pier scour pit under high flow intensity is 27.7% to 38.6% higher than that of low flow intensity, with an average increase of 33.9 %, especially when Lk/D=7D, the increase is about 38.6%. The above shows that the existence of sand pit has an important influence on the local scour of pier. The relationship between the size and morphological characteristics of the pit area corresponding to different pit depths is analyzed. With the increase of the pit depth, the cross-sectional area corresponding to the pit depth of the sand pit is larger ; when the distance between the sandpit and the pier model is closer, the cross-sectional area of the sandpit at the same pit depth is larger, which indicates that the interaction between the sandpit and the pier model leads to the intensification of the shear erosion effect of turbulence on the sandpit. The larger the cross-sectional area of the pier scour pit at the same pit depth, that is, the pit diameter gradually becomes larger. The relationship between the flow field and the scour is studied. As the distance between the sand pit and the pier model is closer, the upstream deceleration of the pier is more obvious in the flow direction and the transverse velocity cloud. In the process of the downstream water flow away from the pier, the velocity increases more slowly, which indicates that the vortex structure is formed when the water flows through the sand pit, which reduces the flow velocity. As the distance between the sand pit and the pier model is closer, the vorticity area in the scour pit upstream of the pier is smaller, but the vorticity in the scour pit is more dense, which will aggravate the sediment transport and make the depth of the local scour pit of the pier larger, resulting in the larger area of the pier exposed, which is not conducive to the safe and stable operation of the pier. The vorticity at Lk/D=7D is about 2.2 times that of Lk/D=0 when there is no sand pit, which also verifies that the vorticity increases exponentially after the turbulent flow passes through the sand pit. In-depth study of the influence of sand mining at different positions in the river on the flow characteristics around the pier. With the increase of the modal order, the energy decreases faster, and the low-order mode is the main carrier of the whole flow field. The first-order mode occupies most of the energy in the flow field and is the most stable mode in the flow structure, while the higher-order mode covers the smaller-scale flow structure.ConclusionsThe results demonstrated with the closer the distance between the sand pit and the pier model and the greater the flow intensity, The greater the depth and cross-sectional area of the scour pit of the pier, but the upstream dip angle of the sand pit is equal and basically consistent with the angle of repose of the sediment. As the distance between the sand pit and the pier model is closer, the maximum pit depth of the pier scour pit gradually increases. When the distance between the sand pit and the pier model is Lk/D=7D, the maximum pit depth of the pier scour pit under high flow intensity is about 38.6 % higher than that under low flow intensity. As the distance between the sand pit and the pier model is closer, the upstream deceleration of the pier is more obvious in the flow and spanwise velocity contours, and the vorticity is more intensive in the scour pit of the pier. When the distance between the sand pit and the pier model is Lk/D=7D, the vorticity at the maximum depth of the scour pit is about 2.2 times that of the non-sand pit i.e. Lk/D=0, which aggravates the local scour of the pier. As the distance between the sand pit and the pier model is closer and the water flow intensity is larger, the first-order mode is smaller. The turbulence around the pier is intense and the energy tends to be more dispersed. As the modal order increases, the energy decay rate increases.